The effectiveness of promotion tools done by One Two Three Communication (M) Sdn. Bhd. for postpaid Celcom Executive Plan 50: case study in Bandar Melaka / Mohd Hafiz Ahmad - Ahmad, Mohd Hafiz (Faculty of Business and Management, 2008)
One Two Three Communication (M) Sdn. Bhd. is the key dealer of Celcom which promotes and sells Celcom's products. In year 2008, the sales for postpaid Celcom Executive Plan 50 (CEP 50) not achieved monthly sales target. Due to that problem matter, researcher do the research study on effectiveness of promotion tools done by One Two Three Communication that come with the objectives to determine is the advertising, sales promotion, public relations and personal selling influence effectiveness of promotion tools. Next, is to measure the level effectiveness of the promotion tools that used by One Two Three Communication and last is to provide recommendations that can help the company to enhance their promotion efforts for postpaid CEP 50. In this study, the researcher used the research design of Descriptive Research and Causal Research. For sampling technique, researcher used Convenience Sampling in Non-Probability for this study. Researcher distributed the questionnaire to respondents randomly around Bandar Melaka to have primary data for data analysis and other sources are from reports journals and so on. Cross Tabulation Analysis and Hypothesis,Test, a clear findings and results are observed showed that the effectiveness of promotion tools were influenced by advertising, sales promotion, public relations and personal selling. By used Regression, the findings shows that the major factor that influenced effectiveness of promotion tools was sales promotion. The researcher also gave some recommendations for One Two Three Communication (M) Sdn. Bhd. To improve their promotion efforts to become more effective.